A ratiometric fluorescent probe for fast detection and bioimaging of formaldehyde. Issue 10 (17th February 2023) - Lin, Nai-Jie; Wu, Huan; Peng, Jing; Yang, Shu-Han; Tan, Rui; Peng, Yu; Wang, Ya-Wen
Abstract : A novel ratiometric fluorescent probe has been developed for rapid detection of formaldehyde based on a new recognition mechanism. Abstract : A novel ratiometric probe (SWJT-10 ) based on isophorone derivatives has been designed and synthesized for the detection of formaldehyde (FA). This probe displayed an obvious ratiometric fluorescence response to FA with a blue shift from the NIR (680 nm) to the yellow light region (600 nm) in aqueous solution. And it showed good selectivity, high sensitivity and a fast response to FA (less than 5 s) due to a new recognition mechanism. Moreover, SWJT-10 has been applied to monitor FA in living cells and zebrafish.